1986
DOI: 10.1093/infdis/154.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Resistance to Imipenem During Therapy for Pseudomonas aeruginosa Infections

Abstract: We studied the mechanism of resistance to imipenem in three clinical isolates of Pseudomonas aeruginosa. Two of these isolates arose from imipenem-susceptible strains isolated during therapy with imipenem and were associated with treatment failure. One of these two strains had previously been broadly resistant to beta-lactams; the second acquired resistance to imipenem alone. One isolate of the third strain was resistant to imipenem but susceptible to other antipseudomonal beta-lactams. No isolate contained be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(136 citation statements)
references
References 28 publications
7
128
0
1
Order By: Relevance
“…SDS-PAGE gel analysis of the OMPs of the representative mutant strain showed a marked reduction in a specific OMP with a molecular weight of about 48,000 (data not shown). These results indicated that the mutant resulted from the reduced expression of OprD and they exhibited reduced susceptibility or resistance to DRPM, MEPM, or IPM compared to the parent strain [3,6,7]. These results also suggested that both MEPM and IPM could specifically select for the carbapenem reduced susceptible mutants or carbapenem-resistant mutants of P. aeruginosa strains, and that DRPM could prevent growth of the mutants at a concentration that would inhibit cell growth.…”
Section: Appearance Of Colonies Of Carbapenem-resistant Mutants Withimentioning
confidence: 84%
See 1 more Smart Citation
“…SDS-PAGE gel analysis of the OMPs of the representative mutant strain showed a marked reduction in a specific OMP with a molecular weight of about 48,000 (data not shown). These results indicated that the mutant resulted from the reduced expression of OprD and they exhibited reduced susceptibility or resistance to DRPM, MEPM, or IPM compared to the parent strain [3,6,7]. These results also suggested that both MEPM and IPM could specifically select for the carbapenem reduced susceptible mutants or carbapenem-resistant mutants of P. aeruginosa strains, and that DRPM could prevent growth of the mutants at a concentration that would inhibit cell growth.…”
Section: Appearance Of Colonies Of Carbapenem-resistant Mutants Withimentioning
confidence: 84%
“…This type of imipenem (IPM)-resistant P. aeruginosa mutant was first isolated during clinical trials of IPM for the treatment of serious infections caused by P. aeruginosa [3]. The IPM-resistant mutants of P. aeruginosa were found to lack a 45 KD to 49 KD protein [3ϳ6] in the outer membrane protein D2 (OprD), which forms a channel specific to IPM and its structural analogues [7].…”
Section: Introductionmentioning
confidence: 99%
“…pHN4 is a recombinant plasmid (blaS tet Xcos+ incP); it codes for production of L-1 3-lactamase, which was originally derived from Xanthomonas maltophilia and is capable of hydrolyzing panipenem and imipenem (19). The recombinant plasmid was transferred to both 3-C and 3-B (19), which were both isolated from a single patient and which were identical in serotype and pyocin type (18). P. aeruginosa PAO1 and its OprD protein-deficient mutant DD-11 were used to determine uptake of ['4C]panipenem into the cells and for susceptibility testing.…”
Section: Methodsmentioning
confidence: 99%
“…However, several recent reports (Quinn et al, 1986;Buscher et al, 1987;Lynch, Drusano & Mobley, 1987) have documented the emergence of imipenem resistance during imipenem therapy of Pseudomonas aeruginosa infections. Such resistance emerged in six of ten cases of nosocomial pseudomonal pneumonia (Salata et al, 1985).…”
Section: Introductionmentioning
confidence: 99%